Design, synthesis and biological evaluation of simplified analogues of the RNA polymerase inhibitor etnangien - Menche, Dirk; Li, Pengfei; Irschik, Herbert (Bioorganic & medicinal chemistry letters, 2010)
Novel simplified analogues of the potent RNA polymerase inhibitor etnangien were obtained by total synthesis and evaluated for antibacterial activity against Gram-positive bacteria and one Gram-negative bacterium.
Erstmals am 23. Dezember 2009 online erschienen
Gesehen am 13.04.2023